Comparison of the anti-duck hepatitis A virus activities of phosphorylated and sulfated Astragalus polysaccharides. Issue 3 (February 2017) - Wang, Yixuan; Chen, Yun; Du, Hongxu; Yang, Jingjing; Ming, Ke; Song, Meiyun; Liu, Jiaguo
Duck hepatitis A virus (DHAV) (Picornaviridae) causes an infectious disease in ducks which results in severe losses in duck industry. However, the proper antiviral supportive drugs for this disease have not been discovered. Polysaccharide is the main ingredient of Astragalus that has been demonstrated to directly and indirectly inhibit RNA of viruses replication. In this study, the antiviral activities of Astragalus polysaccharide (APS) and its derivatives against DHAV were evaluated and compared. APS was modified via the sodium trimetaphosphate and sodium tripolyphosphate (STMP-STPP) method and chlorosulfonic acid-pyridine method to obtain its phosphate (pAPS) and sulfate (sAPS), respectively. The infrared structures of APS, pAPS, and sAPS were analyzed with the potassium bromide disc method. Additionally, the antiviral activities were evaluated with the MTT ((4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2-H-tetrazolium bromide) method in vitro and the artificial inoculation method in vivo . The clinical therapy effects were evaluated by mortality rate, liver function-related biochemical indicators, and visual changes in pathological anatomy. The anti-DHAV proliferation effects of APS, pAPS, and sAPS on the viral multiplication process in cell and blood were observed with the reverse transcription-polymerase chain reaction method. The results revealed that pAPS inhibited DHAV proliferation more efficiently in the entire process of viral multiplication than APS and sAPS. Moreover, only pAPS significantly improved the survival rate to 33.5% and reduced the DHAV particle titer in the blood as well as liver lesions in clinical trials. The results indicated that pAPS exhibited greater anti-DHAV activity than APS and sAPS both in vitro and in vivo .